SURGICAL OUTCOMES IN SECONDARY HYPOSPADIAS PATIENTS IN A TERTIARY CARE CENTRE – OVER A DECADE EXPERIENCE - Mukesh Chandra Arya; Prashant Gupta; Singhal, Ankur; Yogendra Shyoran; Prabhnoor Singh, Ajay Gandhi (Indonesian Journal of Urology, 2023)
Objective: The objective of this study is to analyze the surgical outcomes in secondary hypospadias patients over 10 years in a tertiary care center. Material & Methods: From January 2010 – December 2019, 68 patients with secondary hypospadias were managed in our department. The age at surgery, location of meatus at presentation, associated chordee, meatal stenosis, and fistula were noted. Techniques used for correction and postoperative complications with overall success rate were studied. Primary hypospadias cases (n=303) were excluded from this study. Results: Age varied from 6 months to 32 years (mean - 11.06 years). The most common presentation was dehiscence of repair with resultant hypospadias (n=43) and their meatal position was distal 44.1% (n=30) followed by middle in 14.7 % (n=10) & proximal in 4.4% (n=3) patients after orthoplasty. Chordee was present in 67.64% (n=46) cases. (<30o in 50%, n=34; 30-600 in 14.7%, n=10; >60o in 2.9%, n=2). Also, 17.6% (n=12) patients had urethrocutaneous fistula(UCF) and 19.1% (n=13) patients had meatal stenosis. Urethral closure was done using tubularized incise plate (TIP) alone in 4.4% (n=3) cases, TIP and spongioplasty in 48.5% (n=33) cases. The urethral plate was augmented (Snodgraft) in 26 cases (inner prepuce, n=5 and BMG, n=21). Urethral reconstruction was staged in 10.3% (n=7) cases. Meatoplasty was done in 19.1 (n=13) cases and fistula closure was done in 17.6% (n=12) cases. The success rate in secondary cases was 79.2% in our series. Fourteen patients required revision surgeries of which 7 had UCF (Fistula repair), meatal stenosis (n=1, meatoplasty), Glanular dehiscence (n=5, Glanuloplasty and Meatoplasty), stricture (n=1, urethroplasty). Conclusion: Hypospadias surgery in secondary cases is difficult owing to fibrosis, loss of local tissue, and difficult dissection. Glanular dehiscence was most common followed by fistula in our series. We also reported the effectiveness of buffering layers and urethral augmentation in secondary cases but without statistical significance. Keywords: Secondary hypospadias, urethrocutaneous fistula, chordee.